REVIEWS OF ELECTROCOAGULATION PROCESS ON WASTE WATER TREATMENT TECHNOLOGY - Hernaningsih, Taty (BPPT, 2016)
Waste water treatment by industry usually uses chemicals that may lead to additional environmental pollution load. On the other hand, water demand increases and environmental regulations regarding waste water disposal requirements that apply more stringent. It is necessary for waste treatment technique that accommodate this requirement. Electrocoagulation process is a technique of wastewater treatment that has been chosen because the technique is environmentally friendly. This paper will review some of the research or application electrocoagulation process which is conducted on industrial waste water. Types of industrial waste water that is to be reviewed include: industries batik, sarongs, textiles, palm oil, slaughterhouses, food, leather tanning, laundry, pulp and paper. Overview reviewed in this research include the waste water treatment process in several processing variations such as: change in time, electricity and kind of electrodes. The results of the research with electrocoagulation process in the industry are the removal efficiency of TSS, COD, BOD5, Chrome, phosphate, surfactants, color turbidity influenced by several factors including time, strong current, voltage, distance and type of electrode and pH. The results of the study with electrocoagulation process in the industry is the removal efficiency of TSS, COD, BOD5, chromium, phosphate, surfactant, turbidity color that are influenced by several factors including time, strong current, voltage, distance and type of electrode and pH. It is hoped the information presented in this article can be a reference for similar research for the improvement of research on the process ektrokoagulasi.Key words: elektrocoagulation, removal eficiency, environmental friendly